2008
DOI: 10.1016/j.ejheart.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a heart failure diagnosis in administrative registers

Abstract: Background: The incidence of heart failure is frequently reported using hospital discharge diagnoses. The specificity of a diagnosis has been shown to be high but the sensitivity of a reported diagnosis is unknown. Purpose: To study the accuracy of a heart failure diagnosis reported to the Danish National Patient Registers during routine clinical work. Methods: The patient population consisted of 3644 consecutive patients admitted to all departments in one hospital. Diagnoses reported to the National Patient R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
171
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 229 publications
(173 citation statements)
references
References 11 publications
1
171
1
Order By: Relevance
“…Likewise, 57% of the HF diagnoses were nonspecific, which limited us from making any assumptions as to the direct causal pathway between SA and HF. Positive predictive values of SA and HF diagnoses in the Danish National Patient Registry are high; however, sensitivities are lower, which could have led to an underestimation of our results because of type 2 errors 1, 18…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Likewise, 57% of the HF diagnoses were nonspecific, which limited us from making any assumptions as to the direct causal pathway between SA and HF. Positive predictive values of SA and HF diagnoses in the Danish National Patient Registry are high; however, sensitivities are lower, which could have led to an underestimation of our results because of type 2 errors 1, 18…”
Section: Discussionmentioning
confidence: 70%
“…The following diagnoses were included: hypertensive HF, cardiomyopathy, cardiac insufficiency, left‐sided HF, lung edema, and unspecified HF (Table S1). Two separate studies have validated the HF diagnosis in the Danish National Patient Registry and found positive predictive values of 84% (77.9% for first‐time HF) and 81%, respectively 17, 18…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic codes for all hospital discharges are entered into the IPR with complete coverage from 1987 onwards. A validation of other major diagnoses in the IPR was performed by the National Board of Health and Welfare in 2011, confirming the high validity (up to 85–95%) of major cardiovascular diagnoses 22. The International Classification of Diseases (ICD) is used in all Swedish hospitals.…”
Section: Methodsmentioning
confidence: 83%
“…In addition, when analysing the 20 medical records with an HF diagnosis and without complementary diagnoses as described in Methods section, none represented a missed cardiomyopathy diagnosis at any time. However, in three cases, the ICD codes for cardiomyopathy were recorded in subsequent years, indicating that causation is necessary when interpreting results from the hospital discharge registry 20, 21, 22…”
Section: Discussionmentioning
confidence: 99%